Формування маркетингової стратегії розвитку екологічно спрямованих інновацій в аграрному виробництві - Багорка, Марія Олександрівна; Bagorka, Mariya (Дніпровський державний аграрно-економічний університет, 2015)
Стверджується, що сільське господарство відноситься до найбільш впливових на навколишнє середовище секторів економіки України. Саме тому екологізація аграрного сектору на інноваційній основі розглядається як невід’ємна складова його розвитку. Необхідність екологізації маркетингу випливає з основних тенденцій негативних змін стану навколишнього середовища. Впровадження екологічного маркетингу дасть змогу забезпечити належну якість продукції і зберегти навколишнє середовище. It becomes firmly established that agriculture behaves to the most influential on an environment sectors of economy of Ukraine. The innovative model of development of agriculture puts for a purpose the increase of competitiveness of agrarian enterprises in a production and to sale-marketing to the sphere due to introduction of the newest technologies, types of products and management methods. Therefore the environmentally friendly methods of the agrarian sector of the economy of Ukraine on the innovative basis should be considered as an integral part its development.For the choice of marketing strategy it is necessary to learn influence of factors mikro- and macroenvironment of enterprise, which it is developed for. In their traditional consideration does not take into account the factor of environment. In an order completer to represent the specific of agrarian enterprises, it is necessary to take into account an environment as factor of influence on development of strategy of enterprise.For functioning of agrarian production marketing strategy is major functional strategy, chain which unites industry with an external environment and examines a marketing function as fundamental basis of his activity.The necessity for environmentally friendly marketing results from basic tendencies of negative changes of ecological marketing will provide necessary quality of products and the preservation of the environment.
The formation of marketing strategy of environmentally friendly innovations in the agrarian production
Keywords: маркетингова стратегія; marketing strategy; інновації; innovations; екологізація аграрного виробництва; environmentally friendly agrarian production; екологічний маркетинг; ecological marketing; агропродовольча продукція; agroproducts